2018
DOI: 10.1016/j.econlet.2018.04.030
|View full text |Cite
|
Sign up to set email alerts
|

A portable method of eliciting respect for social norms

Abstract: Recent models of prosociality suggest that cooperation in laboratory games may be better understood as resulting from concern for social norms than from prosocial preferences over outcomes. Underlying this interpretation is the idea that people exhibit heterogeneous respect for shared norms. We introduce a new, abstract task to elicit a proxy for individual normfollowing propensity by asking subjects to choose from two actions, where one is costly. We instruct subjects that "the rule is" to take the costly act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 13 publications
2
58
0
Order By: Relevance
“…Our design does not allow us to cleanly distinguish which of the two factors, rule-following propensity or beliefs, drives the behavior of the bad punishers. However, the result on the norms elicited in the Dictator game and presented in Figure 4 of Kimbrough and Vostroknutov (2018), suggests that there is a connection between being a rule-breaker and believing that behaving selfishly is appropriate. In particular, rule-breakers tend to think that selfishness is more appropriate than rule-followers do.…”
Section: Discussionmentioning
confidence: 95%
“…Our design does not allow us to cleanly distinguish which of the two factors, rule-following propensity or beliefs, drives the behavior of the bad punishers. However, the result on the norms elicited in the Dictator game and presented in Figure 4 of Kimbrough and Vostroknutov (2018), suggests that there is a connection between being a rule-breaker and believing that behaving selfishly is appropriate. In particular, rule-breakers tend to think that selfishness is more appropriate than rule-followers do.…”
Section: Discussionmentioning
confidence: 95%
“…rule perception variable might be subject to reverse causality: not complying with the parking rule might lead to a lower rating of how bad one perceives not following the parking rule, since people want to justify their behavior. In addition, Kimbrough and Vostroknutov (2018) find that φ i and g(1) are correlated, such that individuals with higher preferences of following rules tend to rate actions which deviate from the norm more inappropriate than individuals with a low preference of following rules. Therefore, it might be hard to measure φ i , and g(1) independently from each other.…”
Section: Survey Responsesmentioning
confidence: 93%
“…Participants are explicitly instructed that the rule is to put the balls in Bucket B. Therefore, the task measures willingness to pay a cost to follow an explicit rule, which is interpreted as social norm compliance (Kimbrough & Vostroknutov, 2018). A study using the Rule Following Task found no difference between political liberals and conservatives in rule-following behaviour (Thomsson & Vostroknutov, 2017).…”
Section: Norm Compliance and Punishment Of Norm Violatorsmentioning
confidence: 99%
“…Fischer et al (2020c) use the Rule Following Task developed by Kimbrough & Vostroknutov (2018) to measure whether social conservatives are willing to forego monetary gains in order to comply with an explicit rule they have been told to follow (see Section 2.2 for details on the task). They find that measures of the social dimension of ideology, such as RWA, support for cultural tightness (Jackson et al, 2019), and security and conformity values (Schwartz et al, 2012), are related to rule-following behaviour (whereas SDO is only weakly negatively related to this).…”
Section: Norm Followingmentioning
confidence: 99%